Praktik Iddah Cerai Mati Bagi Wanita Karier - Arrizqi Mabruroh Assadadah; Abid Rohmanu; Ahmad Junaidi (Institut Agama Islam Negeri Ponorogo, 2025)
The phenomenon of career women undergoing the waiting period (‘iddah) after the death of a spouse raises legal and social challenges, particularly regarding the implementation of Islamic rules amid professional responsibilities. This study analyzes the practice of ‘iddah among female teachers at MTs YP. KH. Syamsuddin Duri Sawo and to evaluate the school's leave policy through the lens of maṣlaḥah and maqāṣid al-sharī‘ah. This is qualitative research using a case study approach. Primary data were collected through in-depth interviews with teachers, the principal, and foundation officials, while secondary data came from institutional policy documents and Islamic legal literature. Data collection methods included interviews, observation, and documentation, with data analyzed interactively through reduction, presentation, and conclusion-drawing stages. The results show that the implementation of ‘iddah among the teachers does not fully comply with classical fiqh rules, particularly regarding leaving the house, adorning oneself, and the duration of ‘iddah, yet is practiced within socially and professionally accepted boundaries. The 40-day leave policy the school applies is not ideal in normative terms, but it contains significant benefits in protecting life, intellect, and wealth. In conclusion, the observed practice of ‘iddah can be justified Islamically through the concepts of maṣlaḥah mursalah and maqāṣid al-sharī‘ah, reflecting the flexibility of Islamic law in responding to the realities faced by modern career women.